Designing Learning Media for The Effectiveness of Vocabulary Junior High School - Syarifah Syarifah; Yuyun Bahtiar; Akhmad Kanzul Fikri (APPLICATION: Applied science in Learning Research, 2022)
English is an international language that is indispensable in addition to knowledge of English as well as a means of communication. Learning requires the media to convey it to students. The researcher uses the Research and Development (R&D) method with the ADDIE development process. The purpose of this study was to determine the results of the development of instructional media in the form of PowerPoint hyperlinks as a tool that helps increase students' learning motivation and the effectiveness of learning media in grade 8th. The sample of students in this study were grade 8th students of MTs Bahrul Ulum Tambak Beras Jombang with 12 students’ responses. Data collection instruments used in this study were interviews and questionnaires. The feasibility of the product was tested for media validation and material validation, each of which has a value of 96% for media and 76% for the material. The results showed that students' vocabulary comprehension skills increased after learning with the PowerPoint application. Learning media hyperlinks that have been validated and revised are appropriate as a tool to increase students' learning motivation.